Analisis Semiotika Roland Barthes Dalam Film Jalan Yang Jauh Jangan Lupa Pulang - Yusrina Adzhani; Muhammad Ichsan; Ria Yunita (Jurnal Ilmu Komunikasi Dan Sosial Politik, 2024)
The movie "A Long Way, Don't Forget to Go Home" is one of the drama genre films that focuses on platonic relationships or what is known as non-romantic relationships that occur between Aurora, Honey, and Kit. This movie is a sequel to "One Day We’ll Talk About Today" directed by Angga Dwimas Sasongko and produced by Visinema Pictures. Broadly speaking, this movie tells the story of Aurora who continues her art education in London, where she discovers new things, one of which is the meaning of life. Aurora, who at that time was facing various problems, managed to survive through obstacles while being a nomad in a foreign country after being helped by the figures of Honey and Kit, her two best friends, who both lived as nomads in the country. The presence of Honey and Kit by Aurora's side made her feel comfortable, as they treated her like a sister, and always provided support to her. The platonic relationship between Aurora, Honey, and Kit is shown through their interactions that are full of familiarity and respect for each other without any romantic overtones. They support each other in their journey to find the meaning of life and face life's challenges. In this movie, the platonic relationship is illustrated as a form of friendship that overcomes distance and time. Although the two have different backgrounds and lives, they remain emotionally and spiritually connected. In conclusion, "A Long Way, Don't Forget to Go Home" beautifully illustrates the importance of platonic relationships in our lives, emphasizing that friendship can be a source of strength and deep understanding in the midst of a life full of changes and challenges.